Study on the piezoresistivity of Cr-doped V2O3 thin film for MEMS sensor applications - Michiel Gidts; Wei-Fan Hsu; Maria Recaman Payo; Shaswat Kushwaha; Frederik Ceyssens; Dominiek Reynaerts; Jean-Pierre Locquet; Michael Kraft; Chen Wang (Microsystems & Nanoengineering)
Abstract Cr-doped V2O3 thin film shows a huge resistivity change with controlled epitaxial strain at room temperature as a result of a gradual Mott metal-insulator phase transition with strain. This novel piezoresistive transduction principle makes Cr-doped V2O3 thin film an appealing piezoresistive material. To investigate the piezoresistivity of Cr-doped V2O3 thin film for implementation in MEMS sensor applications, the resistance change of differently orientated Cr-doped V2O3 thin film piezoresistors with external strain change was measured. With a longitudinal gauge factor of 222 and a transversal gauge factor of 217 at room temperature, isotropic piezoresistivity coefficients were discovered. This results in a significant orientation-independent resistance change with stress for Cr-doped V2O3 thin film piezoresistors, potentially useful for new sensor applications. To demonstrate the integration of this new piezoresistive material in sensor applications, a micromachined pressure sensor with Cr-doped V2O3 thin film piezoresistors was designed, fabricated and characterized. At 20 °C, a sensitivity, offset, temperature coefficient of sensitivity and temperature coefficient of offset of 21.81 mV/V/bar, -25.73 mV/V, -0.076 mV/V/bar/°C and 0.182 mV/V/°C, respectively, were measured. This work paves the way for further research on this promising piezoresistive transduction principle for use in MEMS sensor applications.